Comparison of clinical outcomes of trochanteric femoral nail advanced system (TFNA) with and without cement augmentation for geriatric unstable trochanteric fractures: a single-center retrospective cohort study - Yutaro Kuwahara; Genta Takemoto; Hiroshi Fukuoka; So Mitsuya; Ken-ichi Yamauchi (BMC Musculoskeletal Disorders)
Abstract Introduction Unstable trochanteric fractures (AO types A2 or A3) are reported to be risk factors for mechanical failure such as screw cut-out. This study aimed to compare the incidence of implant related complications and functional outcomes between cement augmentation and non-augmentation. Methods Patients at a single institution aged > 60 years who underwent fixation using the trochanteric femoral nail advanced system (TFNA) with or without cement augmentation from 2020 to 2023 were retrospectively analyzed. We evaluated reduction quality and screw position on immediate postoperative radiographs, the occurrence of screw cut-out, and Parker’s mobility score (PMS) as functional outcomes. Results We evaluated 140 patients in the non-augmentation group and 93 patients in the augmentation group. The mean follow-up period was 13.6 ± 5.7 months. The mean age was 86.0 ± 8.1 years in the non-augmentation and 85.2 ± 8.3 years in the cement augmentation group. Patient demographics, including fracture type, were similar in both groups. The screw cut-out rate was seven out of 140 patients (5.0%) in the non-augmentation group, whereas no patients in the augmentation group experienced screw cut-out, and the difference was significant (p = 0.044). All cases which occurred screw cut-out were associated with postoperative poor reduction quality and screw malposition. The mean PMS at the last follow-up was 4.0 ± 3.0 in the non-augmentation group and 4.7 ± 2.7 in the augmentation group, and the difference was not significant (p = 0.187). Conclusions Cement augmentation showed a significant lower screw cut-out rate compared with non-augmentation. This technique could be a more favorable option for osteoporotic unstable trochanteric fractures.